2018
DOI: 10.1007/s12033-018-0120-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene Delivery to Tobacco Root Cells with Single-Walled Carbon Nanotubes and Cell-Penetrating Fusogenic Peptides

Abstract: Development of efficient, easy, and safe gene delivery methods is of great interest in the field of plant biotechnology. Considering the limitations of the usual transfection methods (such as transgene size and plant type), several new techniques have been tested for replacement. The success of some biological and synthetic nanostructures such as cell-penetrating peptides and carbon nanotubes in transferring macromolecules (proteins and nucleic acids) into mammalian cells provoked us to assess the ability of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…By contrast, NPs, such as silicon carbide whiskers (SCW) and mesoporous silica NPs (MSN), have been effectively used to transfer genes into the plant without using other physical methods (Chang et al, 2013). Here, SCW-mediated transformation has been successfully used to transform tobacco (Golestanipour et al, 2018).…”
Section: Advanced Plant Biomolecule Delivery Approaches Via the Application Of Nanobiotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, NPs, such as silicon carbide whiskers (SCW) and mesoporous silica NPs (MSN), have been effectively used to transfer genes into the plant without using other physical methods (Chang et al, 2013). Here, SCW-mediated transformation has been successfully used to transform tobacco (Golestanipour et al, 2018).…”
Section: Advanced Plant Biomolecule Delivery Approaches Via the Application Of Nanobiotechnologymentioning
confidence: 99%
“…Several NPs can penetrate the cell wall (e.g., CNTs and mesoporous silica), whereas other NPs require chemical or physical pretreatments, such as gold NPs and magnetic NPs (MNPs), for genetic cargo delivery into the cells. Meanwhile, NP-mediated passive delivery has been reported with tobacco (Burlaka et al, 2015;Mitter et al, 2017;Golestanipour et al, 2018;Kwak et al, 2019), cowpea (Mitter et al, 2017), and arugula crops (Kwak et al, 2019). NPs and other new materials might serve as useful vehicles for editing systems (Gao, 2021).…”
Section: Advanced Plant Biomolecule Delivery Approaches Via the Application Of Nanobiotechnologymentioning
confidence: 99%
“…Arginine-functionalized SWCNTs have effectively transported GFP encoding pDNA into the tobacco intact root cells. [83] In another effort to transport pDNA, Burlaka et al [12] have shown the internalization of pGreen 0029, a type of pDNA into the plant cell walls of N. tabacum using non-covalent functionalized carbon nanotubes. The engineered callus and leaf explants of N. tabacum achieved significant sprout regeneration with no toxicity at the indicated concentration.…”
Section: Plant Biotechnology and Agriculturementioning
confidence: 99%
“…The delivery of DNA‐PEI‐CNTs complex into the mature leaf cells was confirmed by electron microscopy; NIR fluorescence imaging showed that this cargo carrier was 700 times more efficient than pDNA adsorbed on pristine SWCNTs. Arginine‐functionalized SWCNTs have effectively transported GFP encoding pDNA into the tobacco intact root cells . In another effort to transport pDNA, Burlaka et al .…”
Section: Introductionmentioning
confidence: 99%
“…The nanocomplexes that are formed by the interaction of these transfection agents with nucleic acids provide some protection from nucleases and facilitate cellular uptake by endocytosis or membrane fusion. There have been a number of reports describing the use of transfection agents for delivery to plant cells (Unnamalai et al, 2004, Cheon et al, 2009, Eggenberger et al, 2011, Lakshmanan et al, 2013, Numata et al, 2014, Ziemienowicz et al, 2015, Kimura et al, 2017, Golestanipour et al, 2018, Miyamoto et al, 2019. The efficiency of many transfection agents, however, may be limited by delivery barriers that are unique to plants (Figure 1).…”
Section: Introductionmentioning
confidence: 99%